Analisis Makna Pesan Yang Terkandung Di Dalam Relief Ukiran Bangunan Pura Umat Hindu - Gusti Putu Artika; Dhanurseto Hadiprashada; Neneng Cucu Marlina (UNIVED Press, 2023)
This research was conducted to analyze the meaning of the message contained in the carved reliefs of the Hindu temple building at the Dharma Yatra temple, Rama Agung village. The research method uses qualitative research methods to analyze the meaning of the messages contained in the relief carvings of Hindu temple buildings in the village of Rama Agung using hermeneutic theory. The results of the study show that the meaning of the messages contained in the relief carvings of Hindu temples at the Dharma Yatra temple have meanings that mostly contain religious meanings and social messages and norms that apply in society in the village of Rama Agung. The religious meaning is in the form of the meaning of religious values ​​and religious teachings, especially Hinduism, the meaning of social messages, namely social rules and regulations that apply in the community in the village of Rama Agung and norms or rules have the meaning of traditional law or customary law of Hindus in the Rama Agung village.